Clinical depression prevalence and associated factors among adolescents with sickle cell anemia in dar es salaam, tanzania: a cross-sectional study - Linda Paul Athman; Agnes Jonathan; Fatima Musa; Honesta John Kipasika; Isihaka Mahawi; Florence Urio; Mwashungi Ally; Ritah Mutagonda; Lulu Chirande; Julie Makani; Emmanuel Balandya (BMC Pediatrics)
Abstract Background Depression commonly arises among adolescents who have experienced long-standing psychosocial difficulties, especially those facing chronic illnesses such as sickle cell anemia (SCA). SCA is a global health concern, and Tanzania is one of the countries with a high incidence, estimated at 8,000–11,000 births per year. This study aims to assess the magnitude and factors associated with depression among adolescents with SCA. Methodology A cross-sectional analytical study was conducted on adolescents aged 10–19 years attending sickle cell clinics in referral hospitals in Dar-es-Salaam, Tanzania, from October 2023 to March 2024. Socio-demographic and SCA severity data were collected using pre-structured and pre-tested questionnaires. A validated Patient Health Questionnaire (PHQ-9) tool was used to screen for depression. Univariate and multivariate regression models were used to determine factors associated with clinical depression. A P value of less than 0.05 was considered statistically significant. Results Among the 326 adolescents enrolled and screened, 49 adolescents (15%) had clinical depression, encompassing those in the moderate, moderately severe, and severe depression categories. Overall 216 (53.7%) adolescents exhibited varying degrees of depression, ranging from mild to severe. Specifically, 167 participants (38.7%) had mild depression, 44 (13.5%) had moderate depression, 4 (1.2%) had moderately severe depression, and 1 (0.3%) had severe depression. Painful episodes within the previous 12 months were significantly associated with clinical depression (aOR = 2.49) (95% CI: 1.17–5.29, p = 0.01). Conclusion Depression is common among adolescents with SCA in our setting. Painful episodes experienced within the previous 12 months were significantly associated with clinical depression. This study highlights the need to screen adolescents with SCA for depression and integrate mental health services in sickle cell clinics.